Systemic administration of probiotics reduces the severity of apical periodontitis - Cosme-Silva, L.; Dal-Fabbro, R.; Cintra, L. T.A.; dos Santos, V. R.; Duque, C.; Ervolino, E.; Mogami Bomfim, S. [UNESP]; Gomes-Filho, J. E. (Wiley, 2019)
Aim: To evaluate the effect of systemic administration of probiotics on the severity of apical periodontitis (AP). Methodology: Twenty-four male Wistar rats were used. AP was induced in the maxillary left/right first molars. The animals were arranged into groups: Control, Lactobacillus rhamnosus, and Lactobacillus acidophilus. Probiotics were administered orally for gavage (109 colony-forming units diluted in 5 mL of water for 30 days) during the development of AP. After 30 days, cardiac puncture was performed to analyse the complete blood count. Moreover, microbiological analysis of the root canal contents and saliva was performed. Then, the animals were euthanized and the jaw removed for histopathological and IL-10, IL-1β and IL-6 immunolabeling analyses. After the Shapiro–Wilk test of normality, the Kruskal–Wallis followed by Dunn's test was performed for nonparametric data, and analysis of variance followed by the Tukey test was performed for parametric data (P < 0.05). Results: No significance difference was observed in the blood profiles and in the counts of microorganisms from the saliva samples among the groups (P > 0.05). Total microorganism counts in the root canal, the inflammatory infiltrate and the immunostaining for IL-1β and IL-6 in AP were significantly lower in the probiotic groups when compared with the control group (P < 0.05). IL-10 was significantly more immunolabled in the probiotic groups than in the control group (P < 0.05). Conclusion: Supplementation with probiotics (Lactobacillus rhamnosus and Lactobacillus acidophilus) had a significant effect on the severity of apical periodontitis in rats, demonstrating the anti-inflammatory effect of probiotics on the development of apical periodontitis.
Keywords: biocompatibility; bone sialoprotein; osteocalcin; osteopontin; pulpotomy